Anestesia local por tumescência com lidocaína em cadelas submetidas a mastectomia - Abimussi, C.j.x. [UNESP]; Ferreira, J.z. [UNESP]; Floriano, B.p. [UNESP]; Paes, F. [UNESP]; Perri, S.h.v. [UNESP]; Oliva, V.n.l.s. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2013)
The present study investigated the benefits of tumescent anesthesia with lidocaine in dogs undergoing mastectomy, seeking the patients' comfort and their postoperative recovery. Seven animals, with different weight and breed, who had cancer in the region of mammary chain underwent mastectomy surgery. All animals received the same anesthetic protocol being used as the association between acepromazine and morphine doses of 0.04mg.kg-1 and 0.4mg.kg-1 (IM), respectively. After 15 minutes a catheter was placed in the cephalic vein and induction with propofol 4mg.kg-1 and 0.2mg.kg-1 followed by maintenance with isoflurane anesthesia was done. After instrumentation, we proceeded to the tumescent anesthesia technique with ice-cold solution consisting of Ringer's lactate, lidocaine 2% without epinephrine and adrenaline in a total volume of 15mL.kg-1. The average duration of the procedure was 74±18 minutes. The plasmatic peak of lidocaine was between 30 and 60 minutes after infiltration. The rescue analgesic was performed after approximately seven hours of infiltration. It can be concluded that the tumescent anesthesia with lidocaine should be considered as a constituent of anesthetic and analgesic protocol in dogs undergoing mastectomy surgery providing parameter stability, safety and good quality postoperative recovery.

O presente estudo investigou os benefícios da anestesia por tumescência com lidocaína em cadelas submetidas à mastectomia, visando ao conforto do paciente e à sua recuperação pós-operatória. Foram utilizados sete animais, de peso e raças variadas, que apresentavam neoplasia em região de cadeia mamária e que foram submetidos à cirurgia de mastectomia. Todos os animais receberam o mesmo protocolo anestésico, sendo utilizado como MPA a associação entre acepromazina e morfina, nas doses de 0,04mg/kg e 0,4mg/kg (IM), respectivamente. Após 15 minutos, foi alocado um cateter em veia cefálica e realizou-se a indução com propofol 4mg/kg e midazolam 0,2mg/kg, seguida de manutenção anestésica com isofluorano. Posteriormente à instrumentação, procedeu-se à técnica de anestesia por tumescência com solução gelada composta por ringer lactato, lidocaína 2% sem vasoconstritor e adrenalina, em um volume total de 15mL/kg. Em média, o tempo de duração do procedimento foi de 74±18 minutos. O pico plasmático de lidocaína deu-se entre 30 e 60 minutos após a infiltração da solução. O resgate analgésico foi realizado após sete horas, aproximadamente, da infiltração. Pode-se concluir que a anestesia por tumescência com lidocaína deve ser considerada como constituinte do protocolo anestésico e analgésico de cadelas a serem submetidas à cirurgia de mastectomia, proporcionando estabilidade de parâmetros, segurança e recuperação pós-operatória de boa qualidade.
Tumescent local anesthesia with lidocaine in dogs undergoing mastectomy
Keywords: cães; anestesia balanceada; dor; neoplasias; dogs; balanced anesthesia; pain; cancer